Using Web Quests in teaching foreign languages at higher educational institutions - ISHCHUK, Nataliia; GERTSIY, Alexander; LIESOVYI, Volodymyr (Journal of Education, Technology and Computer Science, 2013)
Although one of the education’s major goals is to find efficient ways to integrate web-based technologies with the traditional teaching methods applied in teaching-learning process, little research has been made in this area. The article provides the study of the educational value of Web Quests in teaching foreign languages at universities, their role in fostering students’ basic competencies and enhancing their critical thinking. Presented is a Web Quest created by first-year students of Vinnytsia Institute of Economics of Ternopil National Economic University with its further detailed description. Provided are some results of the experiment, which prove the didactic efficiency of Web Quests, integrated with other teaching methods, for improving students’ autonomous learning skills.